Alteration agronomic traits performance of sweet potato cultivars from drylands to paddy fields - Sri Umi Lestari; Amir Hamzah; Reza Prakoso Dwi Julianto (Journal of Degraded and Mining Lands Management, 2019)
This study aimed to evaluate changes in agronomic performances of some sweet potato cultivars planted in the rain-fed dry land and paddy fields. Completely randomized block design with three replications on a single factor of 12 sweet potato cultivars was done in two locations. The first location is the rain-fed dry land that formerly planted corn; located in Jatikerto, Kromengan District, and second is an irrigated paddy field that previously planted with rice, located in Wringinsongo, Tumpang District, Malang Regency. All cultivars that planted in both locations were applied to packaged standard cultivation technology for sweet potato. The parameters observed were storage root weight and vines weight (kg/plant), storage root yields and vines yield (t/ha), harvest index (%) and root/shoot ratio to describe the efficiency level of dry matter translocation to storage root. The results showed that there was a change of agronomic performance in sweet potato cultivars that planted between on the dry land and paddy fields, especially for storage root weight, storage root yield (t/ha) and root/shoot ratio. Changes in the sweet potato cultivation in the dry land to paddy fields are shown by an increase in storage root yields ranging from 2-4 times or reach 206 - 417%.